Four-Hand Piano Transcriptions and the Reception of Symphonic Repertoire in Nineteenth-Century Europe - Miller-Kay, Elissa (Malaysian Journal of Music, 2018)
In the nineteenth century, listening to a symphony was a rare and precious treat. Few could afford to attend the symphony regularly, and even those who could would be lucky to hear a favourite work once every few years. There was, however, one way for nineteenth-century music lovers to hear their favourite symphonies anytime on demand: by playing arrangements. Arrangements of symphonies, particularly those for piano four-hands, were phenomenally popular. Amateur musicians would play through arrangements before a concert to familiarise themselves with unknown works and after to re-experience the music they enjoyed. In the twentieth century, recordings took over this function. Today, it is not the sonic magnificence of the orchestra that is rare and precious; it is the act of music-making. This paper examines the roles that four-hand piano transcriptions played in the reception of symphonic repertoire during the nineteenth century and, by way of conclusion, suggests some pedagogical applications of the findings. The history of four-hand piano transcriptions demonstrates the crucial role that active participation in music-making plays in the understanding and enjoyment of symphonic repertoire.